UJI COBA APLIKASI PEMANENAN AIR HUJAN DAN SUMUR RESAPAN DI WILAYAH BOGOR, DEPOK DAN JAKARTA - Herlambang, Arie; Indriatmoko, Robertus Haryoto; Yudo, Satmoko; Samsuhadi, Samsuhadi (Jurnal Air Indonesia, 2010)
Areas of Jakarta, Bogor, Tangerang and Bekasi (Greater Jakarta) is an area with high rainfall (2250 -2500 mm/year). The rain that falls in this region often cause flooding problems in the area of rice fields, settlements and even in downtown. Rain is a gift from God to be utilized to the maximum extent possible for everyday purposes. Rain Water Harvesting is an attempt to capture rainwater that falls on the roof. In this study, use of the roof area of about 300 -500 m2. Precipitation that falls on the roof is channeled and put into storage, by first filtering done to reduce the dirt. The volume of rain water storage for each location is 10 m3, medium intensity rain (15-20 mm/h), sufficient to meet the storage within a few hours. Rain Water Reservoir are equipped with water pump which has a capacity of 25 liters/minute, the water can be used for flushing toilets and spraying crops. If Rain Water Reservoir is full, water overflows into the Artificial recharge well. The results of analysis with Kostiokov calculation method used to calculate the infiltration rate of Artificial recharge well and calculate the cumulative volume of infiltration at the Artificial recharge well. Results of tests conducted are as follows: a). In Depok, the infiltration rate of Artificial Recharge Well is about 12 mm/minute and was relatively stable at 140 minute (2 mm/minute). It also has the ability to recharge 450 liters of water in 140 minutes. b). In South Jakarta, the infiltration rate of Artificial Recharge Well is about 11 mm/minute and was relatively stable at 160 minutes (2.5 mm/minute). Artificial Recharge Well has the ability to recharge 480 liters of water in 160 minutes. c). In Bantarjati, Bogor, Artificial Recharge Well have the highest capacity, namely 45 mm/minute and was relatively stable at 260 minutes (2.5 mm/minute). Artificial Recharge Well has the ability to recharge 1000 liters of water in 150 minutes. Rain Water Harvesting Development Efforts and Artificial Recharge Well very useful to overcome inundation in residential areas, especially during heavy rain, because it can reduce the volume of surface water into the channel simultaneously. Keywords : Rain Water Harvesting, Infiltration, Artificial Recharge.